Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1111/j.1365-3156.2007.01853.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and risk factors for endemic typhoid fever in Uzbekistan

Abstract: Summarybackground To investigate the risk factors for infection with endemic typhoid fever in the Samarkand region of Uzbekistan.methods Case-control study of culture-confirmed bloodstream infection with Salmonella Typhi.Patients were compared to age-matched community controls. Salmonella Typhi isolates were tested for antimicrobial susceptibility.results We enrolled 97 patients and 192 controls. The median age of patients was 19 years. In a conditional regression model, consumption of unboiled surface water o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 36 publications
4
42
1
2
Order By: Relevance
“…However, typhoid fever in endemic settings has been linked with high-dose exposure from multiple sources and therefore the possibility of an extra-familial source cannot be excluded in such cases [37]. Prior antimicrobial usage is reported to be a risk factor for typhoid [37,38]. However, the impact of such antimicrobials on the resistance pattern of the infecting organisms needs to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, typhoid fever in endemic settings has been linked with high-dose exposure from multiple sources and therefore the possibility of an extra-familial source cannot be excluded in such cases [37]. Prior antimicrobial usage is reported to be a risk factor for typhoid [37,38]. However, the impact of such antimicrobials on the resistance pattern of the infecting organisms needs to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…While living in a crowded household was independently associated with typhoid fever [13], routinely washing vegetables [14] and using a latrine for defecation [12] has been found to be protective. Overcrowding probably represents a greater opportunity for person-to-person transmission within households.…”
Section: Transmission and Risk Factorsmentioning
confidence: 99%
“…Interestingly, while prior antimicrobial use has been shown in multiple epidemiological studies to increase the risk of infection with both antibioticresistant and drug-sensitive serotypes of S. Typhi [14,16,17], two recent case-control studies in Turkey and Bangladesh failed to show such a link [12,13]. It is postulated that, in addition to providing a selective advantage to resistant S. Typhi strains, antimicrobial exposure can lead to prolonged alterations in gastro-intestinal flora and a decreased barrier to bacterial colonisation, lowering the dose of Salmonella necessary to cause infection [18,19].…”
Section: Transmission and Risk Factorsmentioning
confidence: 99%
“…42 Again, the habit of washing vegetables and compulsory use of sanitary latrine for defecation have been found to prevent typhoid. 41,43 In a case-control study in Indonesia, paratyphoid fever was found to be associated with consumption of food from street vendors. 44 Excessive antibiotic use causes an increased risk of infection with both drug-resistant and drug-sensitive serotypes of S. typhi, 43,45,46 Interestingly, two recent casecontrol studies in Turkey and Bangladesh failed to show such a link.…”
Section: Aetiologymentioning
confidence: 99%
“…41,43 In a case-control study in Indonesia, paratyphoid fever was found to be associated with consumption of food from street vendors. 44 Excessive antibiotic use causes an increased risk of infection with both drug-resistant and drug-sensitive serotypes of S. typhi, 43,45,46 Interestingly, two recent casecontrol studies in Turkey and Bangladesh failed to show such a link. 41,42 Prolonged antimicrobial use can cause changes in gastro-intestinal flora and a decreased barrier to bacterial colonisation, facilitating Salmonella infection.…”
Section: Aetiologymentioning
confidence: 99%